2012
DOI: 10.1155/2012/812130
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Presentation of BETHSY 6.2TC Test Results Calculated by RELAP5 and TRACE

Abstract: Today most software applications come with a graphical user interface, including U.S. Nuclear Regulatory Commission TRAC/RELAP Advanced Computational Engine (TRACE) best-estimate reactor system code. The graphical user interface is called Symbolic Nuclear Analysis Package (SNAP). The purpose of the present study was to assess the TRACE computer code and to assess the SNAP capabilities for input deck preparation and advanced presentation of the results. BETHSY 6.2 TC test was selected, which is 15.24 cm equival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 6 publications
(8 reference statements)
0
2
0
Order By: Relevance
“…The results of simulation [29] are shown for pressurizer pressure and maximum heater rod temperature in Figure 3 and Figure 4, respectively. For RELAP5 original Ransom-Trapp break flow model the values of 0.85, 1.25 and 0.75 were used for subcooled, two phase and superheated discharge coefficient, respectively.…”
Section: -8mentioning
confidence: 99%
“…The results of simulation [29] are shown for pressurizer pressure and maximum heater rod temperature in Figure 3 and Figure 4, respectively. For RELAP5 original Ransom-Trapp break flow model the values of 0.85, 1.25 and 0.75 were used for subcooled, two phase and superheated discharge coefficient, respectively.…”
Section: -8mentioning
confidence: 99%
“…It was found that the system and component modeling has a strong effect on the LSC behavior and the thermal-hydraulic parameters like the cladding temperature and the water levels of the core, loop seal, and downcomer. Prošek and Berar (2012) simulated the BETHSY 6.2TC experiment with 6-inch cold leg break using TRACE V5.0 patch 1 and RELAP5/MOD3.3 patch 4 codes. In both code simulations LSC was delayed, and the temperature excursion in the core did not occur unlike in the experiment.…”
Section: Introductionmentioning
confidence: 99%